The Effect Organizational Culture, Organizational Commitment and Achievement Motivation on Performance of Lecturers at the Ex-Pekalongan Residence - Sri Wartulas; Sugiyo Sugiyo; I Made Sudana; Tri Suminar (Universitas Negeri Semarang, 2022)
Lecturer performance is basically the performance carried out by lecturers in carrying out their duties as educators. The quality of educational outcomes is highly dependent on the quality of lecturer performance. The purpose of this study is to develop an empirical model to improve lecturer performance. The independent variables of the study consist of organizational culture, organizational commitment, and achievement motivation with the dependent variable being lecturer performance, which is a quantitative study using regression analysis. The research population is lecturers from 17 private universities in Pekalongan Residency, totaling 789 people. The research sample was 258 people using the proportional cluster random sampling technique. The results of the analysis using regression analysis obtained the following results: Organizational culture, organizational commitment, and achievement motivation partially affect the performance of lecturers. The implication of this research is that there is a need for great attention to the achievement motivation of lecturers as the main factor influencing lecturer performance.